Fresh Twigs, Drying Blood, and Popped Corn: The Ephemeral Materiality of Eastern Minyag Ritual Objects - Valentina Punzi (Religions)
The Eastern Minyag is a small community located east of Gangkar Mountain (Chinese: gongga shan) in Southwest China. Their complex rituals, performed by ritual specialists (sutcywu), serve various purposes: diagnosing the causes of individual psycho-physical ailments, investigating the misfortunes affecting entire families, making offerings to the ancestors, and banishing the ghosts of the deceased. While research on the ritual traditions of communities in the Sino-Tibetan borderlands often subsumes Eastern Minyag rituals under the general category of Tibetan Bon, this article adopts a context-oriented approach that highlights the environmental conditions and cosmology of the Eastern Minyag community. Based on ethnographic fieldwork conducted by the author in 2018–2019, the article examines the material aspects of Eastern Minyag rituals occurring in domestic spaces. Specifically, it first explores how natural elements of animal and plant origin are selected and manipulated to create ritual objects. Secondly, it offers an overview of the setups and processes involved in the vivi ritual. Lastly, it reflects on the temporary agency of ritual objects contingent upon their ephemeral materiality.